Mechanical and Tribological Characterization of WC-Co and WC-AISI 304 Composites by a Newly Developed Equipment - Vilhena, Luis (2022)
Tungsten carbide-based composites are, in many cases, the materials of choice in applications requiring high wear resistance. In the present research work, the mechanical characterization of the WC-Co and WC-AISI 304 composites was carried out, with evaluation of the hardness and fracture toughness and tribological characterization of the composites that included the study of friction and wear rate coefficient through unlubricated sliding tests according to the Pin-on-Disc test method. It was possible to correlate the effect of the different binding phases on the mechanical and tribological properties of WC-based composites, and it can be concluded that the system composed by the tribological pair WC-AISI304/100Cr6 was the one that showed the lowest coefficient of friction while the tribological pair WC-Co/Al2O3 was the one that showed the lowest wear rate coefficient.